Oblivion and the role of middle managers in an organizational change - Husser, Jocelyn (Management international / International Management / Gestiòn Internacional, 2014)
The hospital reforms of French health care institutions fall within the scope of the efficient management of the public sector. This paper seeks to describe the oblivion mechanism handled by middle management in an organizational change context through the theory of conventions. The design of the inquiry is based on longitudinal field research conducted over 6 months and is made up of 6 case studies. The results show that oblivion cannot be considered as an empty space to be filled, as suggested by former research. The memory lapse mechanism includes the following steps: reduction, assimilation and gradual integration.